2015
DOI: 10.3389/fphys.2015.00188
|View full text |Cite
|
Sign up to set email alerts
|

Sodium renders endothelial cells sticky for red blood cells

Abstract: Negative charges in the glycocalyx of red blood cells (RBC) and vascular endothelial cells (EC) facilitate frictionless blood flow through blood vessels. Na+ selectively shields these charges controlling surface electronegativity. The question was addressed whether the ambient Na+ concentration controls RBC-EC interaction. Using atomic force microscopy (AFM) adhesion forces between RBC and endothelial glycocalyx were quantified. A single RBC, mounted on an AFM cantilever, was brought in physical contact with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…Since a vast the glycocalyx) and on circulating blood components e.g., red blood cells facilitates frictionless blood flow. Removal of the surface negative charge (as a result of enzyme reaction) enhances red blood cell adhesion to endothelial cells [34]. A similar effect is produced by sodium cation.…”
Section: Glycocalyx and Reactive Oxygen Speciesmentioning
confidence: 64%
See 1 more Smart Citation
“…Since a vast the glycocalyx) and on circulating blood components e.g., red blood cells facilitates frictionless blood flow. Removal of the surface negative charge (as a result of enzyme reaction) enhances red blood cell adhesion to endothelial cells [34]. A similar effect is produced by sodium cation.…”
Section: Glycocalyx and Reactive Oxygen Speciesmentioning
confidence: 64%
“…At Na + concentrations <140 мМ the number of vacant negative charges remains sufficient to maintain adhesion of red blood cells to endothelial lining at a low level. Sodium renders endothelium sticky for red blood cells [34]. Storage of plasma Na + in the glycocalyx (with partial neutralization of negative surface charge) allows one to divide glycocalyx into "good" which has a capacity for Na + accumulation to maintain sufficient negative charge at normal plasma Na + concentration and "bad" when the loss of negative charge increases adverse interactions between endothelium and red blood cells [35].…”
Section: Glycocalyx and Reactive Oxygen Speciesmentioning
confidence: 99%
“…found that the RBC cell surface properties could be partially restored through the dialysis treatment, especially in those individuals with high serum sodium concentrations before the treatment [47]. It has been shown in vitro that sodium concentrations higher than 140 mmol/L impair the glycocalyx and increase adherence of erythrocytes to endothelial cells [48]. In our population the ESS was not significantly altered through the HD treatment itself, possibly due to preHD serum sodium concentrations (137.7 ± 2.4 mmol/L) close to the prescribed dialysate sodium of 137 mmol/L.…”
Section: Discussionmentioning
confidence: 99%
“…For example, application of polyphenolic compounds in vitro [12] and in vivo [16] can influence SS. Also elevated concentrations of plasma sodium can gradually destroy the charged surface layers of endothelium and RBC as recently demonstrated [8,31,32]. Furthermore, SS changes in inflammatory diseases/atherothrombotic processes are likely to occur since endothelial surface layers are known to lose their negative charges under such conditions [33][34][35].…”
Section: +mentioning
confidence: 99%